Clinical Enthesitis in a Prospective Longitudinal Psoriatic Arthritis Cohort: Incidence, Prevalence, Characteristics, and Outcome. Issue 11 (21st September 2017) - Polachek, Ari; Li, Suzanne; Chandran, Vinod; Gladman, Dafna D.
Abstract : Objective: To evaluate the incidence, prevalence, characteristics, disease associations, risk factors, and outcome of clinical enthesitis in patients with psoriatic arthritis (PsA). Methods: The study included patients with PsA followed prospectively. Enthesitis was defined as the presence of at least 1 tender enthesis at 1 of the 18 entheseal sites of the Spondyloarthritis Research Consortium of Canada enthesitis index. Results: Between 2008 and 2014, 281 of 803 patients had enthesitis, providing a prevalence of 35%. A total of 192 patients developed enthesitis during the course of followup, with an annual incidence of 0.9%. Most of the patients had 1 (48.4%) or 2 (32.2%) tender entheseal sites, and the mean ± SD number of sites per visit was 2.03 ± 1.6. The 3 most common sites were at the insertions of the Achilles tendon, plantar fascia on the calcaneus, and the lateral epicondyles (24.2%, 20.8%, and 17.2%, respectively). More active disease (higher actively inflamed joint count, tenosynovitis, and dactylitis), more pain, and less clinical damage were associated with enthesitis. Higher body mass index, more actively inflamed joints, and younger age were risk factors for developing this condition. Enthesitis resolved in most patients without changing treatment. Conclusion: Clinical enthesitis is common, with a period prevalence of 35% of PsA patients. It usually involves only 1 or 2 sites simultaneously. The most common tender sites are at the insertions of the Achilles tendon, plantar fascia, and the lateral epicondyles. More active disease and more pain are associated with enthesitis.